2004
DOI: 10.1529/biophysj.103.038422
|View full text |Cite
|
Sign up to set email alerts
|

Automatic and Quantitative Measurement of Protein-Protein Colocalization in Live Cells

Abstract: We introduce a novel statistical approach that quantifies, for the first time, the amount of colocalization of two fluorescent-labeled proteins in an image automatically, removing the bias of visual interpretation. This is done by estimating simultaneously the maximum threshold of intensity for each color below which pixels do not show any statistical correlation. The sensitivity of the method was illustrated on simulated data by statistically confirming the existence of true colocalization in images with as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
1,327
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,275 publications
(1,348 citation statements)
references
References 29 publications
15
1,327
0
6
Order By: Relevance
“…Background subtraction was performed in MATLAB using a rolling balling approach in which the radius of the ball was selected to be greater than image features (1 µm). A Costes’ approach was used to automate threshold selection for signal isolation and to determine P values for each z-stack [38], where the null hypothesis was randomly distributed signal within the region of interest. This region of interest was defined by manual segmentation of the platelets and collagen fibres using the interference reflectance channel.…”
Section: Methodsmentioning
confidence: 99%
“…Background subtraction was performed in MATLAB using a rolling balling approach in which the radius of the ball was selected to be greater than image features (1 µm). A Costes’ approach was used to automate threshold selection for signal isolation and to determine P values for each z-stack [38], where the null hypothesis was randomly distributed signal within the region of interest. This region of interest was defined by manual segmentation of the platelets and collagen fibres using the interference reflectance channel.…”
Section: Methodsmentioning
confidence: 99%
“…Value of 1 represents perfect correlation, 0 means no correlation. 42,43 It has been reported that R p around 0.91 indicates that two images are almost identical, 44 and R p around 0.75 shows a relatively high degree of co-localization. 45 Tube formation assay.…”
Section: Methodsmentioning
confidence: 99%
“…As shown by the images in Figure 3A, the majority of the electrotransfected pDNAs (blue color) co-localized with dextran (red color). We then quantified the correlation of the two channels by Manders' method, 57,58 which evaluates the fraction of all pixels in a z stack of confocal images from one channel that co-localizes with those from another channel by calculating the Manders' co-localization coefficient (MCC), which varies between 0 (no co-localization) and 1 (perfect co-localization). The Manders' M1 coefficient was 0.277 ± 0.062, indicating that approximately 28% of red pixels co-localized with blue pixels (see also Figure 3B).…”
Section: Electric Pulse-induced Macropinocytosis Of Macromoleculesmentioning
confidence: 99%